Optimization of a directly coupled PV water pump for irrigation purposes - Sabah, Sanjida Hossain (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Master of Science in Electrical and Electronic Engineering, 2020.